2008
DOI: 10.1007/s11101-008-9096-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolates and the clubroot disease: defense compounds or auxin precursors?

Abstract: The clubroot disease is caused by the obligate biotrophic protist Plasmodiophora brassicae and is one of the most damaging for the family of Brassicaceae. Since many economically important crops belong to this plant family, the understanding of mechanisms how the disease is developing, are of high importance. Glucosinolates, a group of secondary plant products in the family of Brassicaceae, have long been associated with clubroot disease symptoms. Measurements showed that several glucosinolates are induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 90 publications
2
28
0
Order By: Relevance
“…Consistent with this hypothesis, comparison of P. brassicae infection of two resistant and two susceptible B. campestris varieties showed that indole glucosinolate production was induced only in the susceptible varieties (Table 4, Ludwig-Müller et al 1997). P. brassicae interactions with crucifers are described in more detail in another review in this issue (Ludwig-Mueller 2008).…”
Section: Plant-pathogen Interactionsmentioning
confidence: 57%
“…Consistent with this hypothesis, comparison of P. brassicae infection of two resistant and two susceptible B. campestris varieties showed that indole glucosinolate production was induced only in the susceptible varieties (Table 4, Ludwig-Müller et al 1997). P. brassicae interactions with crucifers are described in more detail in another review in this issue (Ludwig-Mueller 2008).…”
Section: Plant-pathogen Interactionsmentioning
confidence: 57%
“…Glucosinolates are secondary metabolites that function in plant defense against insects and pathogens (Hopkins et al, 2009;van Dam et al, 2009). Indole glucosinolate was also suggested to be a precursor of auxin (Ludwig-Muller, 2009), a hormone implicated in nodule development (Mathesius, 2008).…”
Section: Other Compoundsmentioning
confidence: 99%
“…It is a rich source of vitamin C and bioactive compounds, such as glucosinolates. The glucosinolates in Brassica crops have been widely investigated, in particular in broccoli, cauliflower, kale, cabbage, Brussels sprouts, turnip, radish and rocket (Baik et al, 2003;Cartea, Velasco, Obregón, Padilla, & Haro, 2008;Charron, Saxton, & Sams, 2005;Jia et al, 2009;Kim & Ishii, 2006;Kushad, Cloyd, & Babadoost, 2004;Ludwig-Müller, 2009;Padilla, Cartea, Velasco, Haro, & Ordás, 2007;Vallejo, Tomás-Barberán, & García-Viguera, 2002;Xu, Guo, Yuan, Yuan, & Wang, 2006). However, only limited information is available for the glucosinolates in Chinese kale.…”
Section: Introductionmentioning
confidence: 99%